Five decades of N2 fixation research in the North Atlantic Ocean - Benavides, Mar; Voss, Maren (Frontiers in Marine Science, 2015)
Dinitrogen (N2) fixation (the reduction of atmospheric N2 to ammonium by specialized prokaryotic microbes), represents an important input of fixed nitrogen and contributes significantly to primary productivity in the oceans. Marine N2 fixation was discovered in the North Atlantic Ocean (NA) in the 1960s. Ever since, the NA has been subject to numerous studies that have looked into the diversity and abundance of N2-fixing microbes (diazotrophs), the spatial and temporal variability of N2 fixation rates, and the range of physical and chemical variables that control them. The NA provides 10-25% of the globally fixed N2, ranking as the third basin with the largest N2 fixation inputs in the world’s oceans. This basin suffers a chronic depletion in phosphorus availability, more aeolian dust deposition than any other basin in the world’s oceans, and significant nutrient inputs from important rivers like the Amazon and the Congo. These characteristics make it unique in comparison with other oceanic basins. After five decades of intensive research, here we present a comprehensive review of our current understanding of diazotrophic activity in the NA from both a geochemical and biological perspective. We discuss the advantages and disadvantages of current methods, future perspectives, and questions which remain to be answered.